Legal Consequences of Defective Murabahah bil Wakalah Contracts: A Study on Financing Proceeds - Rindiani Agustin; Raisya Fauziah; Rafli Wahyudi; Jaenudin; Nasywa Nathani Salsabila (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2024)
Defective contracts in Murabahah bil Wakalah transactions pose significant challenges for Islamic financial institutions, particularly in the management of funds arising from these defects in accordance with Sharia principles. This study aims to investigate whether all funds associated with defective contracts are classified as non-halal or if only the profit margins fall into this category. Additionally, the research seeks to develop strategies for managing these funds in compliance with Sharia provisions. Employing a normative juridical methodology with a qualitative approach, this study focuses on the analysis of regulations and fatwas issued by the National Sharia Council (DSN-MUI). The findings indicate that profit margins derived from defective contracts are classified as non-halal funds and should be allocated for social activities in alignment with Sharia guidelines. Conversely, the allocation of principal funds must be tailored to the specific nature of the transaction. Furthermore, transparent and accountable fund management, bolstered by regular audits, is essential to ensure adherence to Sharia principles while preserving the integrity and public trust in Islamic financial institutions.